2001
DOI: 10.1038/sj.ejcn.1601257
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in relationship of serum leptin and relative weight for the standard in normal-weight, but not in overweight, children as well as adolescents

Abstract: Objective: To demonstrate sexual dimorphism in serum leptin levels not only during puberty, but also in childhood in Japan. Design: Cross-sectional study. Setting: Hamamatsu-Hokuen study in Japan. Subjects: Body weight and height were measured in normal-weight Japanese children and adolescents (143 boys, 178 girls), and 161 boys and 129 girls whose percentage of overweight for the standard (%Wt) was more than þ 25%. Serum leptin levels were compared with %Wt. Subjects were divided into group 1 (6 -10 y of age)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(43 reference statements)
2
10
0
Order By: Relevance
“…37 This sexual dimorphism of leptin was confirmed in our study only in the group of normal-weight individuals (control group), in which females had significantly higher leptin levels compared to males. This is in agreement with the study conducted by Nakanishi et al 36 in which sexual dimorphism in leptin levels and relative weight was found in normal-weight but not in overweight children and adolescents.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…37 This sexual dimorphism of leptin was confirmed in our study only in the group of normal-weight individuals (control group), in which females had significantly higher leptin levels compared to males. This is in agreement with the study conducted by Nakanishi et al 36 in which sexual dimorphism in leptin levels and relative weight was found in normal-weight but not in overweight children and adolescents.…”
Section: Discussionsupporting
confidence: 93%
“…35 This could be explained by the fact that girls gain more fat mass than boys, whereas boys gain more fat-free mass. This marked sexual dimorphism that is present in serum leptin levels at puberty, especially when weight 36 is considered, result from genotype by sex interactions mediated by testosterone. 37 Genes which influence variation in leptin levels are differentially expressed depending on sex and, moreover, sexes show differences in response to the expression of this obesity-related trait to unmeasured residual effects.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported not only clinical aspects of the weight problem 10,11 , but also pathophysiology of the disorders on the basis of endocrinological analyses [12][13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study have found that the levels of serum leptin were high in obese children [3], supporting the fact that leptin resistance is a main mechanism of childhood obesity [4,5], and the expression of the long form of leptin receptor (OBRb) mRNA in the hypothalamus and liver was reduced significantly in dietinduced obese rats [6]. In vitro, leptin at high concentrations down-regulated the expression of OBRb mRNA in HepG2 cells [7], indicating that the silencing of OBRb gene expression played a pivotal role in the mechanism of leptin resistance.…”
Section: Introductionmentioning
confidence: 92%